The Thai Tourist Satisfaction toward National Parks Land in Southern Thailand - Jankingthong, Wiwat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The purposes of this research are to study the Thai tourist satisfaction toward National Parks Land in Southern Thailand and compare of the subjects’ personnel toward the Thai tourist satisfaction. The Population sampling in this research were eight hundred Thai tourists. The instrument for data collection was an accidental sampling and questionnaire. The results of this research revealed that the level of Thai tourist satisfaction toward National Parks Land in Southern Thailand was in all aspects moderate level; goods for sale, facilities, goods and services pricing, traveling comfort, publicity, services rendered by the officials, and the venue’s rules and regulations except that the cleanliness and attractiveness, aspects were at the high level. In term of compares of the subjects’ personnel toward the Thai tourist satisfaction, the results show that their different age, education level, career, monthly income and frequency of visiting did differentiate their level of satisfactions